2012
DOI: 10.1080/00028487.2012.675895
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Migration Timing, Growth, and Survival of Juvenile Coho Salmon in Two Coastal Washington Watersheds

Abstract: Recent improvements in tagging technology allow for the examination of the migration of individual fish, the detection of previously unidentified life histories, and the detailed examination of factors affecting growth, migration, and survival. Using passive integrated transponder tags and instream readers installed near tidewater, we examined the migration, growth, and survival of 18,642 juvenile coho salmon Oncorhynchus kisutch in two small western Washington rivers from 2005 to 2009. In most years, more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 39 publications
4
57
0
Order By: Relevance
“…Chinook Salmon spend more years at sea, so they might benefit more from the survival advantage than do Coho Salmon, for which rapid growth in marine waters is needed to achieve a large size after only a year and a half at sea (Quinn 2005). It should be noted that all the Coho Salmon in the present study were yearling smolts, but subyearlings can be a substantial fraction of wild populations (Roni et al 2012). Subyearlings would enter marine waters at a much smaller size and different time of year (fall versus spring) than yearling smolts, and it is unclear what proportion of them might become residents in Puget Sound.…”
Section: Discussionmentioning
confidence: 88%
“…Chinook Salmon spend more years at sea, so they might benefit more from the survival advantage than do Coho Salmon, for which rapid growth in marine waters is needed to achieve a large size after only a year and a half at sea (Quinn 2005). It should be noted that all the Coho Salmon in the present study were yearling smolts, but subyearlings can be a substantial fraction of wild populations (Roni et al 2012). Subyearlings would enter marine waters at a much smaller size and different time of year (fall versus spring) than yearling smolts, and it is unclear what proportion of them might become residents in Puget Sound.…”
Section: Discussionmentioning
confidence: 88%
“…a Mean of apparent survival and summed proportion survival (which counts fall outmigrants as survivals rather than mortalities; see Roni et al 2012 andHauer 2013).…”
Section: Costs Of Habitat Restoration and Smolt Productionmentioning
confidence: 99%
“…Salmonids in habitats with abundant wood cover or complex pool habitats move shorter distances than fish in simple habitats with little complexity or wood cover (e.g., Bjornn 1971;Giannico and Hinch 2003;Harvey et al 1999;Heggenes et al 1991;Rinne 1982;Wilzbach 1985). Moreover, recent tagging studies on juvenile salmonid movement have indicated that although most fish do not move long distances during low-flow periods in summer and winter, a portion of juvenile salmonids move long distances or emigrate out of watersheds or subwatersheds in fall or winter (Achord et al 2012;Ibbotson et al 2013;Pess et al 2011;Roni et al 2012).…”
Section: Biological Response To Wood Placementmentioning
confidence: 99%